The intelligent approach is used by decision support systems for tourist destinations in North Sumatra - Taufik Abdullah; Jeremia Jordan Sihombing; Maulana Malik Fajri; Debi Yandra Niska (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2024)
The sheer amount of tourism attractions in North Sumatra makes it difficult for visitors to choose where they wish to travel. Tourists can select the ideal place, but they must also deal with a number of issues, such as time and financial limits, which can significantly influence the selection. Therefore, the goal of this study is to assist travelers in selecting the top tourist destination in North Sumatra based on their time and financial constraints. The Simple Attribute Rating Technique (SMART) technique is employed in this study to choose tourist attractions based on four criteria: the measurement of the distance to tourist locations from the city center, the quantity of public tourist facilities, the cost of entrance tickets to attractions, and the daily average of visitors to attractions. The study's findings show that the Decision Support System is competent at handling data and making the best suggestions for tourism attractions. The findings revealed that Sibolangit Forest was the superior alternative in general. Sipiso-piso In addition, waterfall was chosen as the best substitute for places with waterfalls, Lake Toba was chosen as the best substitute for destinations with lakes, and Dua Rasa River was chosen as the best substitute for destinations with rivers. One piece of advice is to compare it to other decision support system techniques and add other factors, such as cleanliness, safety, age, tour kind, and ease of access to tourist attractions